Design and analysis of the solar car body - Yusri, Yusof (2010)
This report shows the design and analysis of body parts for racing solar cars because this play an important role in the motor industry today and solar car also powered by sun energy (solar). This is obtained from solar panels on the surface of the vehicle. Photovoltaic (PV) cells convert the sun's energy directly into electric energy. This is project use the materials type as carbon fiber. Overall, this project involves many processes, starting from the design concept, in this project design is very long time and this part most important in solar car industry. Secondly start the analyzing the parts of the body because the body plays a role in absorbing solar energy as possible as well, the car body design aerodynamic.